Estudos citogenéticos em espécies das tribos Hypostomini e Ancistrini (Loricariidae, Hypostominae) - Rubert, Marceléia (Universidade Federal de São Carlos, 2011)
Conventional and molecular cytogenetic analysis were performed on 15 species of the subfamily Hypostominae, comprising 12 species of the Hypostomini tribe, genus Hypostomus, and three of the Ancistrini tribe, genera Ancistrus and Hemiancistrus. The chromosome number of 2n=52 was observed for Ancistrus multispinis (14m+14sm+24st-a), A. brevipinnis (14m+14sm+24st-a) and Hemiancistrus punctulatus (14m+26sm+12st-a). The nucleolar organizer regions (Ag-NORs) and 18S rDNA sites are simple and terminal for species, A. brevipinnis, A. multispinis and H. punctulatus. In these species, it can be seen that the NORs are also CMA3+/DAPI-. As for the heterochromatin, H. punctulatus showed a small amount of this chromosome component, while A. multispinis and A. brevipinnis showed a larger amount, with large blocks on the long arm of some st-a pairs. In turn, the different species of Hypostomus showed a variation from 64 to 82 chromosomes, exhibiting differences in the karyotype formula between species. The NORs were multiple for most species analyzed, with different phenotypes observed in the number and position, which was also confirmed by FISH analysis, showing an interindividual and interspecific variability. In all species, the NORs were also CMA3+/DAPI _. The heterochromatin pattern distribution was different in each species, being another important chromosome marker. Cytogenetic, molecular, and morphometry analysis were performed in the species Hypostomus albopunctatus (Piracicaba river, SP) and H. heraldoi (Pirapitinga river, GO), including those morphologically similar samples present in the Mogi Guaçu river (SP). All individuals had 2n=74, whereas H. albopunctatus showed 10m+20sm+44st-a and H. heraldoi 8m+20sm+46st-a. These two karyotype formulae were found in the Mogi Guaçu river population. Distinct Ag-NOR phenotypes were observed among the three populations and confirmed by FISH. Regarding the heterochromatin pattern, H. albopunctatus presented terminal bands and an interstitial block. In H. heraldoi, the heterochromatin was found widely distributed in the terminal and interstitial regions of some st-a chromosomes. In these species, the NORs were also CMA3+/DAPI _. RAPD analysis and sequencing of the cytochrome oxidase subunit I (COI) gene were carried out in these two species, in the Mogi Guaçu population and in three more species, H. regani, H. margaritifer, and H. hermanni, obtaining the same dendrogram pattern. All species could be differentiated by their COI sequences, resulting in a total of 16 haplotypes. These analyses, combined with the morphometric data, showed that H. heraldoi and H. albopunctatus are two valid species and the specimens from the Mogi Guaçu river still retain some characteristics of H. albopunctatus, and were provisionally designated as Hypostomus aff. albopunctatus. Due to the large number of species currently included in the Hypostomus genus, along with both the intra and interspecific variability in morphology and color pattern, there are often problems in the taxonomy of this group, which can be assisted by cytogenetic data. This study provided new chromosomal data for Loricariidae, being a valuable cytotaxonomic tool for the Hypostomini tribe. The joint analysis of different characters, such as cytogenetic, molecular, and morphometric, allowed a more precise characterization of different populations of Hypostomus species, helping to clarify their validity as distinct evolutionary units.
Keywords: Citogenética de peixes; Citotaxonomia; Cariotípo; Bandamentos cromossômicos; Topótipos; Neotropical fish; Cytotaxonomy; Karyotype analysis; Chromosome marker; Topotipos; Hypostomus; Ancistrus; Hemiancistrus; CIENCIAS BIOLOGICAS::GENETICA